دراسة وتحليل دور الحكومة في أسواق الخدمات الصحية في البلدان النامية عموماً وفي المنطقة العربية خصوصاً (1995-2005) - قنوع نزار (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إذا كان لدور الحكومة في الحياة الاقتصادية بشكل عام, ما يبرره فهو بكل تأكيد في سوق الخدمات الصحية أقوى حجة وأكثر وجاهة لاعتبارات كثيرة. أهمها حساسية خدمة الصحة, وصلتها الوثيقة بكل الاعتبارات الاقتصادية, والاجتماعية على حد سواء. وعليه فان هذا البحث سوف يتناول بالدراسة والتحليل المبررات الموضوعية لتدخل الدولة في أسواق الخدمات الصحية. ويعرض لكيفية تدخل الحكومة لمعالجة أوجه القصور في قواعد السوق الحر في أسواق الخدمات الصحية. ويتناول شكل الإعانات الحكومية لجانبي الطلب والعرض في سوق الخدمات الصحية. لنخلص في نهاية المطاف إلى عرض جملة النتائج والتوصيات التي يمكن أن تكون مفيدة في هذا الإطار. Generally, if there is a justification for a governmental role in the economic life, it must be in the health service market for many considerations. The most important consideration is the sensitiveness of health service and its relevance to all economic and social considerations. Accordingly, the research studies and analyzes the objective justifications of government intervene in health service market. It presents an approach based on free market rules of government intervention to deal with the insufficiencies of health services market. Mainly, the research focuses on the forms of government grants of that market sides: supply and demand. Finally, it has concludes with a few results and recommendations that could be helpful in this dimension.